Evidence of introgression in Cyprian honey bees (Apis mellifera cypria) through geometric morphometrics analysis - Constantinou, Mamantia; Christofi, Sotiroula; Tsaltas, Dimitris; Papachristoforou, Alexandros (My University, 2025)
The endemic honey bee subspecies Apis mellifera cypria holds significant ecological and economic value in Cyprus but faces an increasing risk of genetic erosion due to the importation of non-native queens. This study applied geometric morphometrics to evaluate wing shape variation in 2400 worker bees from 160 colonies across 15 regions of Cyprus. Nineteen landmarks on the right forewing were digitized and analyzed using Procrustes superimposition, principal component analysis (PCA), and canonical variate analysis (CVA). A population from Lemnos Island, Greece, was used as an out-group. Results showed that 12 Cypriot populations clustered closely, indicating morphological homogeneity, while three populations linked to queen importation exhibited significant divergence. All Cypriot populations were clearly separated from the Lemnos out-group. These findings underscore the effectiveness of morphometric analysis in detecting population structure and support conservation measures to protect the genetic integrity of A. m. cypria.
Keywords: Apis mellifera cypria; Honey bee; Conservation; Geometric morphometrics; Wing shape